Oxidation of the Interiors of Carbide Exoplanets - H. W. Horn; E. Garhart; K. Leinenweber; V. Prakapenka; E. Greenberg; S.-H. Shim (The Planetary Science Journal)
Astrophysical measurements have shown that some stars have sufficiently high carbon-to-oxygen ratios such that the planets they host would be mainly composed of carbides instead of silicates. We studied the behavior of silicon carbide in the presence of water under the high pressure–temperature conditions relevant to planetary interiors in the laser-heated diamond-anvil cell. When reacting with water, silicon carbide converts to silica (stishovite) and diamond at pressures up to 50 GPa and temperatures up to 2500 K: $SiC+2{{\rm{H}}}_{2}{\rm{O}}→ SiO_{2}+{\rm{C}}+2{{\rm{H}}}_{2}$ . Therefore, if water can be incorporated into carbide planets during their formation or through later delivery, they could be oxidized and have mineralogy dominated by silicates and diamond in their interiors. The reaction could produce CH _4 at shallower depths and H _2 at greater depths that could be degassed from the interior, causing the atmospheres of the converted carbon planets to be rich in reducing gases. Excess water after the reaction can be stored in dense silica polymorphs in the interiors of the converted carbon planets. Such conversion of mineralogy to diamond and silicates would decrease the density of carbon-rich planet, making the converted planets distinct from silicate planets in mass–radius relations for the 2–8 Earth mass range.